MODEL PROBLEM BASED LEARNING MENGGUNAKAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA SUBTEMA PERPINDAHAN KALOR DISEKITAR KITA DI KELAS V SD NEGERI 132 PALEMBANG - Imam Adi Nugroho (Jurnal Inovasi Sekolah Dasar, 2021)
This research aims to improve students learning outcomes in the sub-themes of heat transfer around us in 5th-grade students of SD Negeri 132 Palembang. through the application of the Problem Based Learning Model using Audiovisual Media. This research uses the method of classroom action with two cycles of action. Data collection techniques that are used are test and observation. Action class research has four stages namely Planning, implementation, observation, and reflection. The Subject in the research is 5th-grade student of SD Negeri 132 Palembang with a total of 36 students consisting of 20 females students and 16 male students. The results of this research indicate that the completeness of student learning outcomes in the first cycle amounted to 61,11% with an average 64,30%, in cycle II the completeness of student learning outcomes increased to 83.33% with an average of 81.52. From the result of observation, in the first cycle,the percentage of student activity reached 71.45 within the active category, in the second cycle there was an increase of 81.09% within the very active category. So it can be concluded that the application of the Problem Based Learning model using Audiovisual can improve the learning outcomes of students in the heat transfer sub-theme around us in 5th-grade students of SD Negeri 132 Palembang. Keywords: Model Problem-Based Learning, Audiovisual Media, Students learning outcomes